Pengaruh Perceived Value, Customer Satisfaction, Dan In-Shop Emotions Terhadap Repurchase Intention - Kamilah, Muthi'ah; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of perceived value, customer satisfaction, and in-shop emotions on repurchase intention among customers of ZAMA Homewear, a boutique specializing in Malang-style embroidered fashion products. Design/methodology/approach – This study adopts an explanatory research design to analyze the relationships among perceived value, customer satisfaction, in-shop emotions, and repurchase intention. Data were collected through Google Forms from 140 respondents aged at least 18 years who had purchased products directly at ZAMA Homewear boutique at least once. A non-probability sampling method with purposive sampling technique was applied. The data were analyzed using multiple regression analysis, supported by classical assumption tests and hypothesis testing conducted with IBM SPSS Statistics 24. Findings – The results indicate that perceived value, customer satisfaction, and in-shop emotions all have a positive influence on repurchase intention. Higher levels of perceived value, stronger customer satisfaction, and more positive in-store emotional experiences lead to increased likelihood of future repurchase intentions among customers. Originality/value – This study contributes to consumer behavior literature by integrating cognitive (perceived value), evaluative (customer satisfaction), and affective (in-shop emotions) factors in explaining repurchase intention within a local fashion boutique context. The findings provide practical implications for small fashion businesses in enhancing customer retention through value creation, service quality improvement, and emotional retail experiences.